Correlation between Cost of Capital, Book Values and Shares Prices: Evidence from Qatar Stock Exchange - Ibrahim Tahat (Financial Markets, Institutions and Risks)
This study investigates the link between the cost of capital, and both share book values and market prices on Qatari Stock Exchange. The rational of this test suggested that their relationship between the published financial data and decision making as result of complying with transparent disclosure, in capital markets which suggested that this data has lost its value relevance to shareholders. Ohlson (1995) basic equity valuation model applied in this research, which linked to the firm’s equity market value to book values adjusted for abnormal returns. Data used in this study represent all listed firms on Qatari Stock Exchange, to test this assumption for the period from 2010 to 2019. The result indicated a negative correlation among cost of capital and both firms book values and share market prices. Firms bearing higher risks are predicted to earn higher returns. According to the study's findings, statistical evidence supports the claim that raising the amount of leverage raises the risk for equity shareholders. Because of an increase in leverage results in a higher expected return on investment to compensate equity shareholders for the increased risk.